Logic and Faith in for Strengthening the Islamic Education Curriculum: An Analysis of the Thought of Classical Scholars - Rudhi, Rudhi; Tahir, Muhammad Sakti; Herianti, Herianti (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The Islamic Education (IE) curriculum struggles to balance reasoning ('aql) and religion (naql). This conflict between reason and religious texts could lead to a poorly integrated curriculum that separates spiritual and intellectual parts, impeding faith-based critical thinking. Therefore, the purpose of this study is to analyze and identify models of integration between logic and faith in the thought of classical Islamic scholars, as well as to formulate their implications for strengthening and developing a holistic contemporary IS curriculum. This study uses a qualitative approach with textual analysis methods and critical literature studies of key works by prominent classical scholars (such as Al-Ghazali, Ibn Sina, and Ibn Rushd) that explicitly discuss the relationship between philosophy/logic and Islamic sciences (sharia and kalam). Data are analyzed comparatively and interpretively to extract an integrative framework. The results indicate that classical scholars do not separate logic from faith. Logic is considered an essential tool (wasilah) for verifying theological truth, refuting doubts (syubhat), and constructing solid arguments in defense of Islamic doctrine. Their thinking offers an integrative model in which reason serves as a supporter and strengthener of faith (iman), rather than as its opponent. This model emphasizes that the pinnacle of reason lies in recognizing its limits and submitting to revolution. This article presents a theoretical and practical framework for Islamic education curriculum developers to provide critical thinking and logical argumentation resources without sacrificing spiritual depth. This dissertation produces graduates with deep faith and maturity, and integrated reasoning to face modern difficulties.